Pengelompokan Kabupaten/Kota di Pulau Kalimantan Berdasarkan Indeks kemahalan Konstruksi Tahun 2020-2024 Menggunakan Algoritma Spatio Temporal-DBSCAN - Irfan, Muh.; Suyitno, Suyitno; Fathurahman, M. (Program Studi Statistika FMIPA Universitas Mulawarman, 2025)
The Construction Cost Index (CCI) is an indicator that describes the level of cost of construction in a region compared to the national average. The CCI between districts/cities in Kalimantan Island in 2024 still shows a considerable difference. To understand the pattern and similarity of CCI values between districts/cities, a clustering approach is needed. Clustering is a data analysis technique to group data based on similarity. The clustering algorithm used in this research is the Spatio Temporal Density Based on Spatial Clustering of Application with Noise (Spatio Temporal-DBSCAN) algorithm which forms clusters based on density in spatial and temporal aspects simultaneously. The purpose of this study is to obtain the optimal cluster in clustering districts/cities on Kalimantan Island based on spatial aspects (longitude and latitude data) and temporal aspects (IKK value from 2020-2024) based on the Silhouette Coefficient (SC) value of the Eps and MinPts combinations that were tried. Based on the clustering results, 2 clusters and also noise were obtained from the combination of Eps1=2, Eps2=13 and MinPts=8 with an SC value of 0.3179 which means that the optimal cluster formed has a weak structure.